Environmental regulation and horizontal mergers in the eco-industry - Joan Canton; Maia David; Bernard Sinclair-Desgagné (Fondazione Eni Enrico Mattei (FEEM), 2008)
This paper considers the environmental policy and welfare implications of a merger between environment firms (i.e., firms managing environmental resources or supplying pollution abatement goods and services). The traditional analysis of mergers in Cournot oligopolies is extended in two ways. First, we show how environmental policy affects the incentives of environment firms to merge. Second, we stress that mergers in the eco-industry impact welfare beyond what is observed in other sectors, due to an extra effect on pollution abatement efforts; this might lead to disagreements between an anti-trust agency seeking to limit market concentration which can be detrimental to consumer surplus and a benevolent regulator who maximizes total welfare.
Keywords: D62; H23; L11; 330; Eco-Industry; Environmental Policy; Horizontal Mergers; Umweltschutzsektor; Horizontale Konzentration; Umweltpolitik; Soziale Wohlfahrtsfunktion; Theorie